(untitled) (Journal of Education and Development, 2024)
This study examined early childhood preservice teachers’ perceived science teaching efficacy and its association with their teaching beliefs (constructivist and traditional beliefs). The participants included 181 preservice teachers enrolled in an early childhood teacher education program at a university in the Midwestern United States. Information was collected using the Science Teaching Efficacy Beliefs Instrument – Preservice (STEBI-B) and Teaching Beliefs Survey (TBS). The results revealed that the preservice teachers were efficacious about their science teaching, showing a negative relation with traditional teaching beliefs and no statistically significant relation with constructivist teaching beliefs. The results of hierarchical regression analyses revealed that the preservice teachers’ traditional teaching beliefs was a significant negative predictor of their personal science teaching efficacy and of their science teaching outcomes expectancy, while there was no significant effect of constructivist beliefs on them. These results suggest that when preservice teachers adhere to traditional teaching methods, it can lower their confidence and expectations about their effectiveness in teaching science. This underscores the current trend in early childhood education towards promoting innovative, student-centered teaching practices. By moving away from traditional beliefs and embracing more constructivist and inquiry-based approaches, teacher education programs can better prepare preservice teachers to create dynamic, effective, and engaging science classrooms for young children. This approach aligns with contemporary educational practices that prioritize hands-on learning and critical thinking, laying a strong foundation for students’ lifelong interest and involvement in STEM subjects.